Impaired platelet reactivity in patients with septic shock: a proof-of-concept study. (3rd July 2020) - Fogagnolo, Alberto; Taccone, Fabio Silvio; Campo, Gianluca; Montanari, Giacomo; Capatti, Beatrice; Ferraro, Gioconda; Erriquez, Andrea; Ragazzi, Riccardo; Creteur, Jacques; Volta, Carlo Alberto; Spadaro, Savino
Abstract: Coagulation disorders and thrombocytopenia are common in patients with septic shock, but only few studies have focused on platelet variables beyond platelet count. The aim of this study was to evaluate whether platelets reactivity predicts sepsis-induced thrombocytopenia in patients with septic shock. We therefore enrolled consecutive patients with septic shock and platelets count >150*10 3 /μL on the day of the diagnosis. Platelets reactivity tests were performed daily from the diagnosis of septic shock until day five; platelet volume distribution and mean platelet volume were also recorded daily. Sepsis-induced thrombocytopenia was defined as a platelet count <150*10 3 /μL. Thirty patients were included; sepsis-induced thrombocytopenia occurred in 11 (31%) patients. Platelets reactivity and platelet count at day of septic shock diagnosis were not correlated. Patients who experienced thrombocytopenia had lower maximal aggregation at diagnosis than others. Maximal aggregation tests were predictors of thrombocytopenia (AUROC from 0.756 to 0.797, depending on the agonist used). Both platelet volume distribution width and mean platelet volume were predictors of 90-day mortality (AUROC 0.866 and 0.735, respectively). In this pilot study, impaired platelets reactivity was more common in patients who subsequently developed sepsis-induced thrombocytopenia; also, platelet volume distribution width and mean platelet volume were predictors of 90-day mortality.